Role of Th22 Cells in Human Viral Diseases - Gong, Jianguang; Zhan, Huifang; Liang, Yan; He, Qiang; Cui, Dawei (Frontiers in Medicine, 2021)
Naive CD4+ T cells can differentiate into different cell subsets after receiving antigen stimulation, which secrete corresponding characteristic cytokines and thereby exert biological effects in various diseases. Th22 cells, a novel subset of CD4+ T cells, are different from Th1, Th2, Th17, and Treg cell subsets, which have been discovered in recent years. They can express CCR4, CCR6, and CCR10 molecules and secrete IL-22, IL-13, and TNF-α. They are not able to secrete IL-17, IL-4, and interferon-γ (IFN-γ). IL-22 is considered as a major effector molecule of Th22 cells whose functions and mechanisms of regulating cell differentiation have been constantly improved. In this review, we provide an overview of the origin, differentiation of Th22 cells. Moreover, we also describe the interrelationships between Th22 cells and Th17, Th1, and Th2 cells. Additionally, the role of Th22 cells were discussed in human diseases with virus infection，which will provide novel insight for the prevention and treatment of viral infection in human.